Acceptance of Supportive Illustrations for Preparation of Patients for an Orthopedic Telemedical Consultation - Estel, Katharina; Weber, Gordian; Richter, Luise; Hofmann, Marko; Ruckdeschel, Patrick; Märdian, Sven; Willy, Christian; Back, David Alexander (Frontiers in Surgery, 2021)
Introduction: Telemedical video consultations are a powerful support for patient–doctor interactions. For optimal digital settings, explanatory illustrations may be helpful for patients. This study analyzed patients' the attitude of patients to illustrations preparing for an orthopedic telemedical consultation (OTC). Methods: A leaflet with eight illustrations was designed and their acceptance and estimated necessity was evaluated among patients who had experienced an OTC (EXP-group) and others who had not (NOV-group) with a 12-item-questionnaire. Results: Sixty patients participated (n = 30 each group). All illustrations were evaluated positively. The EXP-group gave significantly higher ratings than the NOV-group for improved understanding by the given keywords of the illustrations (p = 0.046), preference for being informed by illustrations than by merely by a pure text (p = 0.023), better feeling of preparation for an OTC by the illustrations (p = 0.005), and the impression of a simplified process of the OTC by the illustrations (p = 0.012). Discussion: While the illustrations were well-accepted by the participants, significant differences were revealed between the valuation of single aspects by patients, depending on a previous experience with an OTC. Therefore, a leaflet with explanatory illustrations may be helpful in preparing patients for an OTC to support the digital patient–doctor contact.